The people themselves : popular constitutionalism and judicial review - Kramer, Larry, 1958- (Oxford University Press, 2004)
The United States Constitution is the foundational document of the longest and most successful democratic experiment in modern human history. It not only serves as the legal bedrock for the world's most powerful nation-state but also, more broadly, reflects that nation's fundamental commitments as a society.; Who then has the authority to interpret a blueprint of such extraordinary influence? Americans have come to treat the Constitution as somehow beyond the purview, even the competence, of the average American citizen. Only lawyers, judges, and academics are deemed fit to state what exactly the Constitution means. This elitist reliance on expert judgement is a radical and troublesome departure from the founding fathers' intent. America's Founding generation, in darling contrast, embraced a; political ideology that celebrated the central role of the "the people" in supplying government with its energy and direction, an ideal that remained at all times in the forefront of their thinking-Federalist and Anti-Federalist alike.; In this groundbreaking interpretation of America's founding and of its entire system of judicial review, Larry Kramer reveals that the colonists fought for and birthed a very different system - and held a very different understanding of citizenship - than Americans believe to be the norm today. "Popular sovreignty" was no historical abstraction nor was the notion of "the people" invoked largely as a flip rhetorical convenience on the campaign trail. Important trials and the prospective passage; of the influentional legislation such as the Alien Act - which granted a president the power to imprison or even deport immigrants - were met with vigorous public debate. The outcomes were greeted with celebratory feasts and bonfires, or riotous resistance. In short, Americans drew a clear parallel; between the law and the lived reality of their daily existence. Theis self-sovreignty in law as much as politics was active not abstract.; With this book, Larry Kramer vaults to the forefront of Constitutional interpretation. In the process, he rekindles the original spark of "we the people", inviting every citizen to join him in enlivening the seemingly deadened sensibilities that mark the relationship between Americans and their constitutional past, present, and future